Genetic diversity and population structure analysis of Forsythia ovata, a Korean endemic, based on genotyping-by-sequencing - Yoo-Bin Lee; Soonku So; Yoo-Jung Park; Halam Kang; Ha-Rim Lee; Jae-Hyeong Kim; Ho-Kwon Gwak; Kyung-Ah Kim; Kyeong-Sik Cheon (PLoS ONE, 2025)
The perennial shrub Forsythia ovata Nakai, native to the Korean Peninsula, has a highly restricted natural habitat, occurring only in a small area within the Baekdudaegan Mountain Range located in Gangwon-do Province. These characteristics give this species high conservation value, but there is a significant lack of genetic concerning about its populations for conservation purposes. In this study, we utilized genotyping-by-sequencing (GBS) to examine the genetic diversity and population structure of F. ovata. Our analysis including 5,017 single nucleotide polymorphisms (SNPs) from 72 individuals, representing nine distinct populations. The results revealed a mean expected heterozygosity (He) of 0.212, indicating a moderate level of genetic diversity within the species. Additionally, a relatively low levels of genetic differentiation (FST) and high gene flow (Nm) between populations were detected. The analysis of molecular variance (AMOVA) results indicated that most genetic variation occurred within individuals, accounting for 86.66% of the total variance. In contrast, only 6.90% and 6.44% of the molecular variance was attributed to differences among individuals and between populations, respectively. Considering the results of Bayesian structure analysis on the basis of ∆ K, principal coordinate analysis and phylogenetic analysis, we propose two management units for conservation. In addition, given the current conditions faced by F. ovata, both in situ and ex situ conservation should be considered for some populations (SG and BD).